Is Minimally Invasive Spinal Surgery Superior to Endoscopic Spine Surgery in Postoperative Radiologic Outcomes of Lumbar Spine Degenerative Disease? A Systematic Review - Patel, Kashyap; Harikar, Mandara Muralidhar; Venkataram, Tejas; Chavda, Vishal; Montemurro, Nicola; Assefi, Marjan; Hussain, Namath; Yamamoto, Vicky; Kateb, Babak; Lewandrowski, Kai-Uwe; Umana, Giuseppe E. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Minimally invasive spinal surgery (ESS) are both well-established surgical techniques for lumbar spinal stenosis; however, there is limited literature comparing the efficacy of the two techniques with respect to radiologic decompression data.Methods In this review, PubMed, Google Scholar, and Scopus databases were systematically searched from inception until July 2022 for studies that reported the radiologic outcomes of endoscopic and minimally invasive approaches for decompressive spinal surgery, namely, the spinal canal area, neural foraminal area, and neural foraminal heights.Results Of the 378 articles initially retrieved using MeSH and keyword search, 9 studies reporting preoperative and postoperative spinal areas and foraminal areas and heights were finally included in our review. Of the total 581 patients, 391 (67.30%) underwent MISS and 190 (32.70%) underwent ESS. The weighted mean difference between the spinal canal diameter in pre- and postoperative conditions was 56.64 ± 7.11 and 79.52 ± 21.31 mm2 in the MISS and ESS groups, respectively. ESS was also associated with a higher mean difference in the foraminal area postoperatively (72 ± 1 vs. 35.81 ± 11.3 mm2 in the MISS and ESS groups, respectively), but it was comparable to MISS in terms of the foraminal height (0.32 ± 0.037 vs. 0.29 ± 0.03 cm in the MISS and endoscopic groups, respectively).Conclusions Compared with MISS, ESS was associated with improved radiologic parameters, including spinal canal area and neural foraminal area in the lumbar spinal segments. Both techniques led to the same endpoint of neural decompression when starting with a more severe compression. However, the present data do not allow the correlation of the radiographic results with the related clinical outcomes.
Keywords: minimally invasive spinal surgery; spinal endoscopy; degenerative spinal disease; lumbar spinal decompression